Understanding the Effects of Antipsychotics on Appetite Control - Mukherjee, Sayani; Skrede, Silje; Milbank, Edward; Andriantsitohaina, Ramaroson; López, Miguel; Fernø, Johan (Frontiers in Nutrition, 2022)
Antipsychotic drugs (APDs) represent a cornerstone in the treatment of schizophrenia and other psychoses. The effectiveness of first generation (typical) APDs are hampered by so-called extrapyramidal side effects, and they have gradually been replaced by second (atypical) and third generation APDs, with less extrapyramidal side effects and in some cases improved efficacy. However, the use of many of the current APDs have been limited due to their propensity to stimulate appetite, weight gain and increased risk for developing type 2 diabetes and cardiovascular disease in this patient group. The mechanisms behind the appetite-stimulating effects of the various APDs are not fully elucidated, partly because their diverse receptor binding profiles may affect different downstream pathways. It is critical to identify the molecular mechanisms underlying drug-induced hyperphagia, both because this may lead to development of new APDs, with lower appetite-stimulating effects, but also because such insight may provide new knowledge about appetite regulation in general. Hence, in this review we discuss the receptor binding profile of various APDs in relation to the potential mechanisms by which they affect appetite.